Effects of 6% Oil Corn Dried Distillers’ Grains with Solubles Withdrawal Strategies on Finishing Pigs Growth Performance, Carcass Characteristics, and Diet Economics - Jamil E. G. Faccin; Mikayla S. Spinler; Rachelle M. Lazaga; Katelyn N. Gaffield; Robert D. Goodband; Jordan T. Gebhardt; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 1,080 finishing pigs (PIC 337 × 1050; initially 39.2 ± 1.22 lb) were used in a 125-d study to investigate growth performance, carcass characteristics, and economics of pigs fed diets with different DDGS-withdrawal strategies using 6% oil corn DDGS. Pigs were housed in mixed-sex pens, with 27 pigs per pen and 10 pens per treatment. Four dietary treatments were tested, including a control treatment with no DDGS throughout the entire trial, a treatment with 20% DDGS fed for the entire trial, or two treatments evaluating DDGS-withdrawal strategies. The first withdrawal strategy included diets with 20% DDGS for 55 days and then 10% for the rest of the study (20/10%), and the second withdrawal treatment included diets with 20% DDGS until day 105 then 0% until the end (20/0%). The experiment was a randomized complete block design with initial weight as blocking factor. Pens of pigs were weighed every two weeks to determine ADG, ADFI, and F/G. Three weeks prior to the end of the trial, four of the heaviest barrows in each pen were marketed and carcass characteristics and iodine value (IV) were collected. The remaining pigs were marketed at the end of the study and carcass characteristics were also collected. For the first three diet phases (0 to 55 d), pigs fed 20% DDGS had lower ADG (P = 0.040) than pigs fed without DDGS but similar ADFI (P = 0.782), which resulted in poorer feed efficiency (P = 0.038). From 56 to 105 d, no differences (P > 0.05) were observed for ADG, ADFI, and F/G. Overall, pigs fed diets without DDGS throughout the whole trial had improved feed efficiency (P = 0.023) by approximately 2.4% compared to all other treatments; however, ADG and ADFI were similar between treatments. Pigs fed 20/0% DDGS had greater (P < 0.005) removals than other treatments. Pigs fed diets without DDGS throughout had lower removal rate than 20/10% with pigs fed 20% DDGS throughout intermediate. No differences (P > 0.05) were found for mortality rate. When DDGS were fed to pigs, feed cost per pig and per lb of gain were lower (P < 0.05) than when pigs were fed 0% DDGS. However, all four treatment strategies resulted in similar (P > 0.05) revenue and IOFC. For carcass characteristics, in the first marketing event, no differences (P > 0.05) were observed for yield, HCW, backfat and loin depth, and lean. However, pigs fed 0% DDGS had lower (P < 0.001) IV than the others, suggesting better fat quality. In the last marketing event, pigs fed 20/10% DDGS had greater (P = 0.033) backfat depth than those fed 20% with the other treatments being intermediate. This fact resulted in a tendency (P = 0.054) for lower lean percentage for pigs fed 20/10% DDGS compared to the treatments. For HCW, yield, and loin depth, no differences (P > 0.05) were observed. In conclusion, feeding 6% oil corn DDGS to grow-finishing pigs, whether throughout the entire period or with a withdrawal strategy, decreased early growth performance and overall feed efficiency compared to pigs fed diets without DDGS. Overall growth, feed intake, carcass yield, HCW, and loin depth were similar between all dietary treatments, but feeding diets with DDGS worsened fat quality expressed by the higher IV. Finally, even though not statistically different, pigs fed diets without DDGS generated a numerically greater IOFC than treatments fed DDGS throughout the whole period or when applying a withdrawal strategy.
Keywords: dried distillers’ grains with solubles; iodine value; swine; withdrawal strategy